Improvement of enterprise risk visualization: risk mapping - Abdelatif, Aib; Nettour, Djamel; Chaib, Rachid; Verzea, Ion; Bensehamdi, Salim (Technology audit and production reserves, 2023)
The object of the study is the risks that disrupt the accomplishment of any enterprise's missions. Therefore, mastering these risks is a significant asset for organizations and the overall health of the enterprise. Thus, working comprehensively on organizational risk prevention enables the enterprise to formulate a strategy aimed at guarding against all risk factors. Simultaneously, it identifies areas where more targeted actions need to be undertaken, potentially leading to positive changes within the company. To achieve this and allow for a robust and reliable assessment for better governance of harmful elements in the enterprise, we have used the risk mapping method. It is a data visualization tool aimed at highlighting vulnerabilities in various processes and activities that an organization faces, even allowing for informed decisions to prevent and cope with risks. Risk mapping is defined as the approach of identifying, evaluating, prioritizing, and managing risks inherent in an enterprise's activities. It even delves into a thorough investigation of all managerial, operational, and support processes that activities require implementing. This mapping technique is based on an objective, structured, and documented description of existing risks. The assessment allows for a more detailed analysis of initial and residual risks at all levels of the enterprise, thereby facilitating the development of a prioritized action plan accompanied by an analysis of its funding. This obligation is part of a continuous improvement approach to the quality of life and working conditions, even engaging in a sustainable management process. As a case study, we have chosen to focus on the SAIDAL Group of Constantine. Through this case study, we aim to illustrate the practical implications and benefits of using risk mapping as a strategic tool for risk management in a complex organizational context. Now, having a risk map not only promotes a proactive approach to risk mitigation but also contributes to broader goals of continuous improvement and sustainable risk management practices: a necessity for any enterprise.